THE LAND REHABILITATION OF MINE OUT AREA OF SAND QUARRY IN CIKALAHANG VILLAGE, DUKUH PUNTANG DISTRICT, CIREBON REGENCY - Siti R. Untung (Balai Besar Pengujian Mineral dan Batubara tekMIRA, 2009)
The sand quarry activities in Cikalahang Village, District of Dukuhpuntang, Cirebon Regency had been illegally mined by hundreds of people. The land properties are owned by the Cikalahang Village. Those mine areas are close to the Telaga Remis (Remis Lake) , which is administratively included in the Kuningan Regency. The existence of illegal mining has disturbed both of local government and people community. In the regional government point of view, the illegal mining will not significantly contribute to generate regional income, whilst for many people their mining activities will produce a destruction to the environment. These can be seen from the objection of the people that request the government to stop all of mine activities because of disturbance to environmental condition of the Telaga Remis (Remis Lake) as one of the water resources for the Cirebon Regency. Based on the intensity of the people requirements, the government of Cirebon Regency had decided to close all of activities of the illegal mining in those area in 2006. According to the decision of Cirebon Regent and the Office of Environment, Forestry and Mining Cirebon Regency, it had prepared planning for rehabilitation and restoration to recover the natural and environmen- tal capability in the mined out areas with respect to the regional spatial planning, land utilization and community demand. The intention of study is to analyse the currently condition of environment in those area including people perception and then making further evaluation to obtain the properly environmental pic- tures for determining the real and strategic action. Data resources to support the study were collected through primary and secondary data. The primary data of physical-chemical component can be obtained by taking instantaneous samples of soil and surface water in the area of study. To identify the people perception, some questioners have been spreaded out to the various strata of people in order to obtain their perception and also direct interview will be applied in this study. The secondary data required for this study such as regional spatial planning, regional landuse and regional regulations will be taken from some institutions in Cirebon Regency. Result analyses showed that the soil characteristics in mined out area were poor because of lack of nutrient and high porousity and the water of Telaga Remis and mine out area could be used as fishing cultivation and household water. The final study shows that the mined out area can potentially be developed as tourism resort in accordance with people request. The other consideration this area is adjacent to Telaga Remis with the background of the beautiful panorama of Mount Ciremai.